Does financial crisis give impacts on Bahrain Islamic banking performance? a panel regression analysis - Hidayat, Sutan Emir; Abduh, Muhamad (Canadian Center of Science and Education, 2012)
The 2007/2008 global financial crisis has given a significant impact on the performance of banking industry worldwide. The objective of this study is to see the impact of global financial crisis towards the financial performance 0f Islamic banking industry in Bahrain. Moreover, it also utilizes bank specific factors as predictors for Islamic bank performance in Bahrain. Panel regression is used to analyze the data. The result shows that LTA, LEQ, and LOHE are significant bank specific factors to influence Islamic bank performance in Bahrain. In addition, there is no significant impact of financial crisis upon the financial performance during the crisis period; however, it does affect the financial performance of Bahrain Islamic banking industry after the crisis period.